Preface for the Special Issue "Trends in Educational Gamification: Challenges and Learning Opportunities" - José Carlos Piñero Charlo; Nadja Belova; Eduardo Quevedo Gutiérrez; Alberto Zapatera Llinares; Elena Arboleya-García; Jakub Swacha; Paula López-Serentill; Enrique Carmona-Medeiro (MDPI AG, 2022)
Readers of the journal Education Sciences probably agree that playing games comes naturally-we all know how to play some game-however, because of the complexity of gaming, it is almost exclusively limited to mammals with regard to all animals: almost 80% of mammals use some sort of game for learning [...]